Electrocatalytic Nitrogen Reduction Performance of Si‐doped 2D Nanosheets of Boron Nitride Evaluated via Density Functional Theory. Issue 4 (15th January 2021) - Guo, Zhongyuan; Qiu, Siyao; Li, Huan; Xu, Yongjun; Langford, Steven J.; Sun, Chenghua
Abstract: Electrochemical nitrogen fixation under ambient conditions is proposed as a sustainable alternative to the traditional Haber‐Bosch method to combat both a global energy crisis and climate change. However, effective catalysts for electrocatalytic nitrogen reduction reaction (eNRR) under ambient conditions, a crucial part for the electrocatalysis system, still face large challenges of low Faradic efficiency (FE) and low yield of ammonia. Here, we propose Si‐doped BN 2D nanosheets (BNNS) as a new class of metal‐free catalysts, and computationally study their performance in eNRR by density functional theory (DFT). The calculations show that the Si atom in the boron‐edge site exhibits the highest activity with the over‐potential (η) of 1.06 V from the first hydrogenation step, which is close in value to the benchmark of this reaction, the flat Ru(0001) surface (η=0.92 V). Moreover, Si‐doping can greatly enhance the conductivity of pristine BNNS, making it a good candidate for electrocatalysis. Overall, this research opens up a new direction of designing high‐performance Si‐based 2D catalysts for dinitrogen fixation beyond the hotspot research of boron‐ or transition metal‐based catalysts. Abstract : Si‐doped 2D Nanosheets : Si atoms in the boron‐edge of BN can offer η=1.06 V towards eNRR as a low‐cost metal‐free catalyst.